The Digital Divide and Media Literacy: a Critical Approach - Jandrić, Petar (Array, 2011)
The digital divide is the division between information haves and have-nots. A typical approach to the digital divide consists of interpreting population statistics. Positivist approach provides valuable data that significantly improves our understanding of the problem. In order to reach beyond surface of the problem, however, positivist approach should be replaced by a more holistic view that takes into account various technological, social, historical and other parameters (Castells, 2003 ; Mason i Hacker, 2003: 40). On such basis, van Dijk and Hacker develop a critical approach to the digital divide that identifies four kinds of barriers to access to information and communication tehnologies and the type of access they restrict: 1. Lack of elementary digital experience caused by lack of interest, computer anxiety, and unattractiveness of the new technology (“mental access”). 2. No possession of computers and network connections (“material access”). 3. Lack of digital skills caused by insufficient userfriendliness and inadequate education or social support (“skills access”). 4. Lack of significant usage opportunities (“usage access”) (van Dijk & Hacker, 2003: 315-316). In this presentation we shall analyze each kind of barriers in the context of media literacy. On such basis we shall develop recommendations that could tighten the gap between information haves and have-nots, and develop media literacy on both sides of the digital divide.